2021
DOI: 10.35762/aer.2021.43.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Consequence of Seawater Intrusion on Soil Properties in Agricultural Areas of Nonthaburi Province, Thailand

Abstract: Seawater intrusion associated with climate change and sea level rise (SLR) has been postulated for the last decade that causes negative impact on worldwide environmental resources. In Thailand, however; the pertaining information to its effect on soil properties in agricultural areas has not been clearly reported yet. Hence, this study aimed to investigate the seawater intrusion effect on soil properties in agricultural areas of Nonthaburi Province, Thailand. Five study locations, which anticipated to be affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…The impacted GDP (PPP) accounts for 96% of Bangkok's total GDP (PPP) and is the highest among seven major Asian cities (Hong Kong, Tokyo, Jakarta, Seoul, Taipei, and Manila) [102]. Negative impacts of seawater intrusion on soil, crop productivity and municipal water in the Lower Central Plain of Thailand were also documented [68][69][102][103]. A recent study has confirmed that the groundwater quality in the Lower Chao Phraya River Basin in Thailand has deteriorated due to salinization caused by seawater intrusion [104].…”
Section: Potential Impacts Of Soces In Thailandmentioning
confidence: 99%
“…The impacted GDP (PPP) accounts for 96% of Bangkok's total GDP (PPP) and is the highest among seven major Asian cities (Hong Kong, Tokyo, Jakarta, Seoul, Taipei, and Manila) [102]. Negative impacts of seawater intrusion on soil, crop productivity and municipal water in the Lower Central Plain of Thailand were also documented [68][69][102][103]. A recent study has confirmed that the groundwater quality in the Lower Chao Phraya River Basin in Thailand has deteriorated due to salinization caused by seawater intrusion [104].…”
Section: Potential Impacts Of Soces In Thailandmentioning
confidence: 99%
“…The seawater intrusion on agricultural soil properties in Nonthaburi increased the electric conductivity (EC) and sodium adsorption ratio (SAR) to approximately 0.21-4.38 dS m −1 and 8.29-41.89, respectively, which are higher than the annual average value [7]. Moreover, in the northeast of Thailand, approximately 17% of its land area is affected by salt from rock salt and the accumulated effects from human activities [8].…”
Section: Introductionmentioning
confidence: 99%